THE INFLUENCE OF INTERNAL AND EXTERNAL FACTORS ON THE EFFECTIVENESS OF EFFECTIVE CLASS MANAGEMENT - Azizah, Siti Nur; Almunajjah, Syalipah; Galya, Tazkia Jauhara; Diniyati, Tazkya; Iskandar, Sofyan (LPPM Univ. Ibn Khaldun Bogor, 2026)
Education plays a crucial role in shaping character, fostering creativity, and enhancing discipline in students. Learning success is largely determined by the teacher's skill in optimally and effectively organizing and controlling the classroom, aiming to create a conducive learning atmosphere that fosters enthusiasm and fosters students' creative potential. The effectiveness of classroom management is influenced by several factors, both internal and external. Internal factors include psychological aspects such as self-awareness, interest, motivation, and a positive mindset. Students with high motivation and self-awareness tend to be more active and responsible. Learning success is largely determined by the teacher's skill in optimally organizing and controlling the classroom. Research shows that the most dominant external factors are a lack of parental supervision and support, as well as a community environment that does not support discipline. Therefore, the main conclusion is that teachers must take a strategic role in balancing these internal and external influences. This can be achieved through the implementation of planned, collaborative, and contextual classroom management strategies, an inclusive, participatory learning environment, and one that supports the development of student creativity.